THE SETTLEMENT OF CONFLICT ON LAND OCCUPATION AND OWNERSHIP (Case Study Between PT. (Persero) Pelabuhan Indonesia II Cabang Panjang and Community in Pidada Village, Panjang Sub District and Way Lunik Village, Telukbetung Selatan Sub District, Bandar Lampung Municipality) - SUBAGYO (NIM 25106311), JOKO
The conflict of land occupation and ownership between PT. PELINDO II Cabang Panjang with community of Kalurahan Way Lunik Teluk Betung Selatan Kota Bandar Lampung is one of the conflict that has taken place for a long time and has not been settled yet until now although a lot of settlement efforts have been done by each party. This research is a socio-legal research, namely, the field research which has its purposes to find out the facts and data as a material to explain the cause of conflict, the form of conflict and the efforts that have been done to settle the conflict of land occupation and ownership between PT.(Persero) PELINDO II Cabang Panjang with the community in Kalurahan Pidada Kecamatan Panjang and Kalurahan Way Lunik Kecamatan TelukBetung Selatan Kota Bandar Lampung. The analysis in this research is done by using descriptive-qualitative referring to the existing concepts and theories, namely, the land giving theory, conflict theory, and the theory of land conflict resolution to get answers of the research questions. .The result of this research is that the giving of management right to PT. PELINDO II Cabang Panjang by BPN contrary to the existing regulation. Based on the field study, part of the HPL land belongs to PT PELINDO II Cabang Panjang has been occupied by the community for housing purpose. The land conflict arises from the different interests and this is an open conflict. The efforts of conflict settlement have been done, namely, by using an alternative dispute resolution in the form of formal complaint and negotiation. The formula of conflict settlement are to give the right of land ownership to the community in Pidada Village, Panjang Sub District and Way Lunik Village Teluk Betung Selatan Sub District.